Applications of Integrating Wildlife Habitat Suitability and Habitat Potential Models. (18th February 2021) - Williamson, Chad R.; Campa, Henry; Locher, Alexandra B.; Winterstein, Scott R.; Beyer, Dean E.
ABSTRACT: Assessment of habitat suitability provides natural resource managers with insights on the quality and spatial distribution of habitat for wildlife species. However, habitat suitability models only provide information on current habitat parameters, and do not consider changes in habitat due to forest succession and disturbances. Habitat potential models have been developed by identifying habitat types and their successional trajectories to provide insights on how landscapes change with time. We developed habitat suitability index (HSI) models and habitat potential models for elk ( Cervus elaphus nelsoni ) on public and private lands within the Michigan elk range (1, 220 km 2 ) in northeastern lower Michigan, USA. Our objective was to demonstrate how integration of habitat suitability and habitat potential models can provide spatiotemporal insights on wildlife habitat. When constructing public‐lands models, we used state forest compartment‐inventory data to identify cover types important to elk, and assigned suitability values (0 = low, 1 = high) to each cover type for elk life requisites (i.e., spring food, winter food, winter thermal cover). Additionally, we modified suitability values based on stand conditions acquired from state forest inventory records (e.g., stand size, percent canopy closure, age of aspen [ Populus spp .]). For our private‐lands models, we used satellite imagery to classify cover types and assigned suitability values to cover types for each elk life requisite, and modified values based on percent canopy closure for winter thermal cover. Elk habitat potential was modeled by delineating habitat types by overlaying digital spatial data layers (soils, land‐type associations, vegetation) and identifying successional trajectories using habitat classification guides and literature. We assigned suitability values to each habitat type for life requisites at early to late successional stages. The highest suitability value of each habitat type's successional stage determined the habitat potential for each habitat type. Our winter thermal cover HSI model indicated several large areas (5–13 km 2 ) of high suitability (i.e., lowland conifers) in the southern third of our study area. Our winter food HSI model indicated a heterogeneous arrangement of high suitability areas (hardwoods, upland conifers, aspen) throughout our study area. Our spring food HSI model indicated few areas of high suitability (openings) primarily on private lands. Our habitat potential models indicated high potential for each elk life requisite across the elk range. Comparisons between current elk habitat suitability and habitat potential identify key areas where managers can maximize management efforts for elk in Michigan. Areas determined to have high habitat potential (e.g., mature aspen stands) may become focus areas if they currently have low habitat suitability. Conversely, managers can avoid committing resources to areas with low habitat potential. Integrating habitat suitability and potential models provides insights on how wildlife habitats may respond to forest succession, land management practices, and disturbances, and ultimately help natural resource professionals prioritize and meet a diversity of wildlife management goals. © 2021 The Wildlife Society. Abstract : We developed habitat suitability index models and habitat potential models for elk on public and private lands within the Michigan, USA, elk range during 2018 in order to demonstrate how integration of habitat suitability and habitat potential models can provide spatiotemporal insights on wildlife habitat. The integration of these models provides insights on how wildlife habitats and species may respond to forest succession, land management practices, and disturbances, and ultimately help natural resource professionals meet a diversity of wildlife management goals.